2005
DOI: 10.1063/1.2006216
|View full text |Cite
|
Sign up to set email alerts
|

Polarization of strained BaTiO3∕SrTiO3 artificial superlattice: First-principles study

Abstract: We performed first-principles calculation to investigate the effect of epitaxial strain on lattice instabilities and polarization behavior of BaTiO3∕SrTiO3 artificial lattice with very short stacking period, i.e., BaTiO31unitcell∕SrTiO31unitcell(BTO∕STO). The structural analysis of BTO∕STO artificial superlattice under in-plane compressive state showed enhanced stability of the tetragonal phase. On the other hand, the stability of monoclinic phase was enhanced when the BTO∕STO was in the in-plane tensile state… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
13
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(14 citation statements)
references
References 21 publications
1
13
0
Order By: Relevance
“…We find that the coupling of local modes with the epitaxial in-plane strain is much smaller, i.e., g x,y z = −2.4 and 3.1 eV/ Å 2 for BTO and STO, than the coupling with the out-of-plane strain, i.e., g zi z = −92 and −59 eV/ Å 2 for BTO and STO, respectively. 16 Analysis of H eff shows that ͑a͒ the polarization P z reduces with tensile strain for all superlattices, consistent with results of earlier first-principles calculations 17 and ͑b͒ the effect of interfacial term becomes strongly enhanced with tensile strain ͓see Fig. 1͑b͔͒.…”
supporting
confidence: 86%
“…We find that the coupling of local modes with the epitaxial in-plane strain is much smaller, i.e., g x,y z = −2.4 and 3.1 eV/ Å 2 for BTO and STO, than the coupling with the out-of-plane strain, i.e., g zi z = −92 and −59 eV/ Å 2 for BTO and STO, respectively. 16 Analysis of H eff shows that ͑a͒ the polarization P z reduces with tensile strain for all superlattices, consistent with results of earlier first-principles calculations 17 and ͑b͒ the effect of interfacial term becomes strongly enhanced with tensile strain ͓see Fig. 1͑b͔͒.…”
supporting
confidence: 86%
“…It was reported that the relaxed ST/BT superlattices may possess symmetries lower than tetragonal. 6,7,10,11,14 However, the tetragonal symmetry in the BT layer is still retained with the polarization along the out-of-plane direction. It should be noted that the BT layers are still under an in-plane compressive strain even though the superlattice is fully relaxed with respective to the ST substrate.…”
Section: ͑1͒mentioning
confidence: 99%
“…7,13 Along with these experimental developments, recent progress in computational methods [14][15][16] have provided us with opportunities to systematically investigate these FE oxide SLs as well. [17][18][19][20] Especially, Nakhmanson et al performed ab initio calculations combined with a genetic algorithm technique to optimize the arrangement of individual BTO, STO, and CTO layers in a SL form, and found that (BTO)n/(CTO)n SLs, where n is the number of unitcells (u.c.) in each BTO and CTO layers, reach the highest polarization for the largest value of n when perfect strain is maitained.…”
mentioning
confidence: 99%